CDM potential of wind power projects in India - Pallav Purohit; Axel Michaelowa (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2007)
So far, the cumulative installed capacity of wind power projects in India is far below their gross potential (È 15%) despite very high level of policy support, tax benefits, long term financing schemes etc, for more than 10 years etc. One of the major barriers is the high costs of investments in these systems. The Clean Development Mechanism (CDM) of the Kyoto Protocol provides industrialized countries with an incentive to invest in emission reduction projects in developing countries to achieve a reduction in CO2 emissions at lowest cost that also promotes sustainable development in the host country. Wind power projects could be of interest under the CDM because they directly displace greenhouse gas emissions while contributing to sustainable rural development, if developed correctly. Our estimates indicate that there is a vast theoretical potential of CO2 mitigation by the use of wind energy in India. The annual CER potential of wind power in India could theoretically reach 86 million tonnes. Under more realistic assumptions about diffusion of wind power projects based on past experiences with the government-run programmes, annual CER volumes by 2012 could reach 41 to 67 million and 78 to 83 million by 2020. The projections based on the past diffusion trend indicate that in India, even with highly favorable assumptions, the dissemination of wind power projects is not likely to reach its maximum estimated potential in another 15 years. CDM could help to achieve the maximum utilization potential more rapidly as compared to the current diffusion trend if supportive policies are introduced.
Keywords: 330